Protocol and programme factors associated with referral and loss to follow-up from newborn hearing screening: a systematic review - Allison R. Mackey; Andrea M. L. Bussé; Valeria Del Vecchio; Elina Mäki-Torkko; Inger M. Uhlén (BMC, 2022)
Abstract Background An effective newborn hearing screening programme has low referral rate and low loss to follow-up (LTFU) rate after referral from initial screening. This systematic review identified studies evaluating the effect of protocol and programme factors on these two outcomes, including the screening method used and the infant group. Methods Five databases were searched (latest: April 2021). Included studies reported original data from newborn hearing screening and described the target outcomes against a protocol or programme level factor. Studies were excluded if results were only available for one risk condition, for each ear, or for < 100 infants, or if methodological bias was observed. Included studies were evaluated for quality across three domains: sample, screening and outcome, using modified criteria from the Ottawa-Newcastle and QUADAS-2 scales. Findings from the included studies were synthesised in tables, figures and text. Results Fifty-eight studies reported on referral rate, 8 on LTFU rate, and 35 on both. Only 15 studies defined LTFU. Substantial diversity in referral and LTFU rate was observed across studies. Twelve of fourteen studies that evaluated screening method showed lower referral rates with aABR compared to TEOAE for well babies (WB). Rescreening before hospital discharge and screening after 3 days of age reduced referral rates. Studies investigating LTFU reported lower rates for programmes that had audiologist involvement, did not require fees for step 2, were embedded in a larger regional or national programme, and scheduled follow-up in a location accessible to the families. In programmes with low overall LTFU, higher LTFU was observed for infants from the NICU compared to WB. Conclusion Although poor reporting and exclusion of non-English articles may limit the generalisability from this review, key influential factors for referral and LTFU rates were identified. Including aABR in WB screening can effectively reduce referral rates, but it is not the only solution. The reported referral and LTFU rates vary largely across studies, implying the contribution of several parameters identified in this review and the context in which the programme is performed. Extra attention should be paid to infants with higher risk for hearing impairment to ensure their return to follow-up.